Differences in the Same OMI/MLS Aura Tropospheric Ozone Data Set Published Before and After January 2013 - Cionco, Rodolfo Gustavo (2015)
On the website "NASA Goddard Homepage for Tropospheric Ozone", global data of tropospheric ozone obtained from observations of OMI and MLS Aura satellite instruments, are reported. In mid-2013, the data was covering the period between October 2004 and January 2013. Subsequently, in early 2014, the time series was extended until December 2013. At present time, the published series has been extended to December 2014. Analysing this new series, we observed that the data already published to January 2013 had been replaced; not only the missing months of 2013 were added but all the values published since 2004 were recalculated. We present the detected differences in the comparison between common data to both time series (the original, before January 2013, and the new one, currently published on the website). These differences are important considering that they represent the result of the same satellite observation and should be considered when comparing results before/after January 2013, especially when adopting a certain confidence level in the spectral analysis of these data to intraseasonal scale. A warn of caution is suggested in the use of these observations and intercomparison with other values of these and other instruments, because of possible recurrent problems of instrumental calibration.